Sample analysis of organically produced honey and conventionally produced honey in Western Serbia - Veroslava Stanković; Coghill Tamara Galonja; Saša Janković; Dušanka Paunović; Snežana Zlatanović (Zaštita Materijala)
Conventional method of honey production is widely spread in the area of western Serbia. Despite the advantages of honey production in an organic manner, beekeepers are still hesitant to take this step, regardless of the difficulties with placement of such honey on the foreign market, so their products are mainly sold on the domestic market. Besides the undeniable nutritional value, honey produced in the conventional way with proper use of agro technical measures and implementation of the wide range of products in the treatment of bee diseases, in its composition very often contain residues of hazardous chemical compounds, pesticides, antibiotics. Research on four qualitative differences of the content of certain substances between the conventional and organic honey producers has been conducted in western Serbia. The research obtained five manufacturers, out of which two were engaged in organic manner of production, while the remaining three dealt with the conventional honey production. After examining the area and the apiaries in question, interviews with honeybee producers, the sampling of honey took place. Upon performed analysis, it was concluded that one conventionally produced sample of honey was not safe for human consumption, due to presence of pesticides.